LDL CHOLESTEROL CONTROL IN PATIENTS FROM A HYPERTENSION CLINIC. (June 2018) - Marques, P.; Morai, T.; Lume, M.J.; Tavares, S.; Silva, C.; Nogueira-Silva, L.; Lima, M.J.
Abstract : Objective: The evaluation and follow up of hypertensive patients requires the consideration of all cardiovascular risk factors such as the lipid profile, particularly the LDL cholesterol. Hypertensive patients usually gather other risk factors that make them high and very high risk patients requiring aggressive LDL control. We aimed to stratify the cardiovascular risk profile from patients evaluated during a year and their LDL control. Design and method: Retrospective study based on clinical records from patients evaluated in Hypertension clinic of a tertiary care hospital during a year. Demographic, biometric and clinical data were gathered. We used the European Society of Cardiology Heart Score to determine the category of risk in 10-years time of our patients and also the exceptions considered in the European Society of Cardiology guidelines. Student t tests and chi-square test were used to compare continuous and categorical variables, respectively. Results: A total of 228 patients, 55% females, aged 60.4 ± 15.9 were evaluated in a year. 31 patients (13.6%) were classified as low risk, 39 (17.1%) as moderate risk, 21 (9.2%) as high risk and 133 (58.3%) as very high risk. 35% patients were classified using Heart Score, 30% had established cardiovascular disease and 20% were diabetic and hypertensive patients. 30% of patients did not receive a statin at the moment of observation. Of the 144 patients classified as high or very high risk 26% didn't receive a statin and only 26% received a high potency statin. Association with ezetimibe was only used at baseline in 3 patients. At baseline LDL control was accomplished in only 38% of patients. In high and very high risk patients only 19% of patients were controlled at baseline. Only 23 patients from the high/very high risk population (15%) were receiving a high potency statin and were not controlled. High salt diet, body weight, risk category and Obstructive sleep apnea were associated with poor LDL control. Conclusions: Many patients evaluated in our Hypertension Clinic were classified as high or very high risk patients. LDL control is markedly insufficient partly due to unawareness and non compliance with European guidelines.